MEMORY MAKING: H.M. SOEHARTO IN THE MANDALA MONUMENT OF WEST IRIAN LIBERATION IN MAKASSAR - Ilmi, Fadhilah Utami (Kementerian Pendidikan dan Kebudayaan, 2021)
This research took an example of memory making by raising the role of Soeharto in the Mandala commando and the establishment of a monument located in the center of Makassar to commemorate the operation of the struggle for West Irian from the Dutch in 1961. This operation was led by General Soeharto, then it is called the Mandala Monument due to this operation’s name. There were many stories of the greatness of Mandala Operation and the Indonesian soldiers in seizing West Irian from the Dutch. This research used qualitative research with observation and literature study of data collection methods. From this research result, the researcher concluded that establishing the historical monuments functioned to commemorate the events of Indonesian history. Several monuments were also established as an appreciation, so that the role of Suharto in several movements can be remembered. The establishment of the Mandala Monument was not only to commemorate the death of the soldiers who were victim in the struggle for West Irian, but also a form of political memory towards the increasing prestige of the father of establishment in the state.